Miracles On Maple Hill Virginia Sorensen ; Illustrated by Beth and Joe Krush - Sorensen, Virginia; Krush, Beth; Krush, Joe (San Diego Harcourt Brace, 1984)
Marly and her family share many adventures when they move from the city to a farmhouse on maple hill
American Corner
Newbery Medal Winner 1957
11
Keywords: English Fiction; English Stories; Pennsylavania -- Fiction